(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teachers are the furthermost essential part of our education system and the character constructors of our nation. Teachers are important to communicating values, ethics, potentials, information, assistances and tasks to our nation’s children. To be a good teacher, they have to go through a practice before entering in real teaching. The school internship is a hands-on experience for the B.Ed trainee. School Internship Programme includes all the activities such as classroom teaching as well as all the school-based activities which the internee have to complete within the course period. The study highlighted about components of two-year B.Ed or Bachelor of Education course under Dibrugarh University of Assam. The internship mixes theory and practice, preparation and ringing the lessons in teaching. The internship program delivers a possibility for the student-teacher to appreciate the numerous features of school and assistances to recover teaching skills in real situations (Parveen, 2012; Jogan 2019). Mishra (2015) conducted a study on internship of two year B.Ed curriculum. In his study discuss about the model frame work developed and implemented by the Mizoram University. Khetavat and Sarvankar (2017) also emphasized about problems faced by the student-teachers of during practice teaching of B.Ed course. The main objective of the study was to study about problems faced by student teacher in internship using survey method. They found that some problems like lack of support from school, lack of communication with students, management of students and time etc. Das and Chowdhury (2019) conducted a study on practice teaching of B. Ed students. The objectives are to determine the level of supervision given to internees by supervisors and mentors, examine the problems, issues and activities of teacher trainees in practice teaching and to establish benefits of the internship program to internees. They have used stratified random sampling technique. They found fine worth training is not available from trainee, less use of innovative teaching methods etc. Deka (2016) highlighted about issues in teacher education in Kamrup district of Assam. One of the objectives is to study views of teacher educators and teacher trainees. Descriptive survey has done using questionnaire and interview. The study found that some main hurdles like not enough staff, untrained teacher educators and lack of financial resource etc. Being a main part of teacher education, practice teaching helps to expansion actual teaching-learning experience.